Working with Microsoft Visual Studio 2005 - Skibo, Craig (Microsoft Press, 2006)
This is not a book about how to use Microsoft Visual Studio 2005, but rather a book that shows how to adapt it to work best for you. Visual Studio 2005 includes a range of tools that allow customization of the development environment. This book shows how to use editors and macros, the add-in architecture, the programmable user interface, and other extensibility features to make repetitive development tasks easier and give programming teams common tools.